The autonomy of pleasure : libertines, license, and sexual revolution - Steintrager, James A., 1965- (Columbia themes in philosophy, social criticism, and the arts., 2016)
What would happen if pleasure were made the organizing principle for social relations and sexual pleasure ruled over all? Radical French libertines experimented with this idea during the Enlightment. They wrenched pleasure free from religion and morality, from politics, aesthetics, anatomy, and finally reason itself, and imagined how such a world would be desirable, legitimate, rapturous -- and potentially horrific. This book ties the Englightenment engagement with sexual license to the expansion of print, empiricism, the revival of skepticism, and fashionable arts and lifestyles of the ancien régime, and the rise and decline of absolutims. It examines the consequences of imagining sexual pleasure as a sovereign power and a law unto itself across a range of topics.